Convergence of children´s depression rating scale-revised scores and clinical diagnosis in rating adolescent depressive symptomatology - Michael G. Koelch; Ferdinand Keller; Nina Sproeber; Joana Straub; Alexander Schneider; Jasmin Grieb; Paul L. Plener (Mental Illness)
The Children´s Depression Rating Scale- Revised (CDRS-R) is a widely used instrument for research on depression in minors. A raw score of ≥40 has often been used as indicator of depressive symptomatology. As a validated German version of the CDRS-R has recently became available, we assessed CDRS-R raw summary scores of a video taped interview session in two different rater groups and compared them with clinical ratings of International Classification of Diseases (ICD- 10) depression diagnosis as observed by a third independent group. We found that for the German version a raw score between 35 and 40 is indicative for mild depressive symptomatology as described by the ICD-10. CDRS-R scores show potential clinical applicability to deduct levels of depression.